Seismic evaluation of reduced beam section frames considering connection flexibility. (17th January 2012) - Ghassemieh, M.; Kiani, J.
SUMMARY In the present article, the seismic performance of frames with reduced beam section (RBS) connections is evaluated. A key purpose of this study is the inclusion of connections flexibility in the seismic performance of RBS frames. Almost in every research projects carried out on seismic performance and design of RBS frames, the beam‐to‐column connection is typically assumed as fully rigid. The results of nonlinear finite element analysis performed on investigating the local performance of RBS connection reveal that they are within the American Institute of Steel Construction‐defined semirigid connections. Three building frames, including 4, 8 and 16 stories considering the semirigid connection as well as fully rigid connection, are considered. A numerical study of the overall seismic response of the building frames subjected to near as well as far field earthquake ground motions using nonlinear static and/or nonlinear dynamic analysis is presented. Results in terms of inter‐story drifts, total drifts, story shears and shear deformation in panel zone indicate that overlooking the flexibility of beam‐to‐column connections may lead to erroneous conclusions and unsafe seismic behavior that subsequently become significant in some cases. Copyright © 2012 John Wiley & Sons, Ltd.